Respuesta :
Answer:
f(x) = 100 - 68x
Step-by-step explanation:
function of x is f(x). Isolate y then replace y with f(x).
680x + 10y - 1000 = 0
680x + 10y = 1000
10y = 1000 - 680x
y = (1000 - 680x)/10
y = 100 - 68x
f(x) = 100 - 68x
We want to rewrite the given expression as a function of x.
We will get: y = f(x) = 68*x + 100
Remember that a general function is something of the form:
y = f(x).
So what we need to do is just isolate y in one side of the given expression.
We start with:
680*x + 10*y - 1000 = 0
Now we need to isolate y:
680*x + 10*y = 1000
10*y = 680*x + 1000
y = (680*x)/10 + 1000/10
y = 68*x + 100
So we have:
y = f(x) = 68*x + 100
This is the function of x that we wanted.
If you want to learn more you can read:
https://brainly.com/question/14418346